Global optimisation of the production of complex aluminium tubes by the hydroforming process. (May 2015) - Bihamta, R.; Bui, Q.-H.; Guillot, M.; D'Amours, G.; Rahem, A.; Fafard, M.
Abstract: With the recent development of analysis software products, designers and engineers are able to design more complex parts to obtain better performance in the final products. In this study, the tube hydroforming process, including preceding processes, i.e. variable thickness tube drawing and two-step bending, are globally optimised to obtain parts without any problems like bursting or un-filled zones at the end of the forming processes. Unlike most previous studies which searched for an optimum hydroforming process by changing two hydroforming parameters, i.e. axial load feeding and internal pressure, in this study, the distribution of initial tube wall thickness and the variation of thickness due to bending steps will be taken into account in a global optimisation algorithm. The developed algorithm is a general-purpose algorithm that can encompass different processes and change various parameters in each process to be able to reach the global objective. The case study used was a part that needs two-step variable thickness tube drawing, and two bending steps before hydroforming. To verify the numerical results in each forming stage and at the end of all forming processes, extensive experiments were performed, and acceptable agreements were observed.